Integrating Viral Hepatitis Prevention Services into an Urban STD Clinic: Denver, Colorado - Subiadur, Julie (Association of Schools of Public Health, 2007)
The Centers for Disease Control and Prevention recommends integrating viral hepatitis prevention services with services for adults evaluated for sexually transmitted diseases (STDs). The Denver Public Health STD clinic began hepatitis B vaccination in 1999, hepatitis C virus (HCV) antibody (anti-HCV) testing in 2000, and hepatitis A vaccination in 2002. Rapid human immunodeficiency virus (HIV) testing began in late 2004. Hepatitis B vaccinations peaked in 2003 (31/100 client visits) when a full-time nurse was hired to vaccinate and eligibility was expanded. The proportion of clients documented to have received their anti-HCV test results declined from an average of 71% in 2000–2003 to 22% in 2004–2005, coinciding with the introduction of rapid HIV testing. Viral hepatitis prevention services can be incorporated into a busy STD clinic if staff and resources are available. Rapid HIV testing may be associated with lower receipt of anti-HCV test results.